(untitled) (Bangladesh Journal of Agriculture, 2023)
The study was conducted to assess the impact of climate change on lemon production at Sreemangal of eastern Bangladesh as the area is moderately vulnerable to climate change. The study sample consisted of 80 randomly selected lemon growers who were interviewed and the data were collected to identify their perceptions, social characteristics, and the impact of climate change on lemon production. The results of the survey indicated that the grower’s perception of climate change was impactful as a majority of growers claimed increased annual precipitation (48.8%), increased summer temperature (48.8%), and reduced winter temperature (46.3%). In the case of extreme events, 56.3% of growers mentioned that the intensity of storms has increased in the last 5 years (2015-2019) and 58.8% of lemon growers said that the intensity of rainfall had increased substantially. However, in terms of environmental hazards, the findings indicate that excess rainfall, pest infestation, cloudy skies, hail storms, and drought are the major problems in lemon production. On the surface, overcast skies cause most of the damage to lemon production. Apart from this, soil fertility, pests, diseases, excess temperature, crop sowing time, maturity period, and drought had a significant impact on lemon production in the study area. From the correlation coefficient table, it appears that many socioeconomic characteristics were also influenced by the impact of climate change on lemon production. In the study area, there is a positive significant relationship between changes in lemon production and changes in environment and risks. The lemon crop requires moderate temperatures and average rainfall for improved production. Bangladesh J. Agri. 2022, 47(2): 64-70